Anxiety in Jiu-Jitsu athletes: differences according to age and competitive level (Research, Society and Development, 2020)
The aim of this study was to analyze pre-competitive anxiety based on the age range and competitive classification of 26 jiu-jitsu athletes aged 25.5 ± 5.24 years. The instrument used was the Competitive State Anxiety Inventory-2 (CSAI-2). Data analysis was conducted using the Shapiro-Wilk, independent Student's t-test, Pearson's correlation and simple linear regression (p